Benjini’s analogy in the light of the efforts of the Iraqi students - Abdullah AI.Waeli , Nahla (Journal of College of Education, 2020)
The impact of Ibn Jenni is not hidden in modern grammatical studies, and Iraqi scholars have a share of this interest, and this research dealt with analogy with Ibn Jenni, who is considered one of the origins of grammatical thinking in light of the efforts of Iraqi scholars to show their views in this field; As there is more than one researcher who detailed the saying about this origin with Ibn Jinni, including Dr. Fadel Al-Samarra’i in (Ibn Jinni Al-Nahwi), Dr. Hossam Saeed Al-Nami in “The Phonetic and Phonological Studies of Ibn Jinni” and Dr. Hassan Salman Hussein in “The Spread in the Language of Ibn Jinni” And Dr. Mustafa Hamid Mustafa in (the grammatical origins of Abu Ali Al-Farsi and Ibn Jinni(